The Energy question : an international failure of policy. - Erickson, Edward W.; Waverman, Leonard (University of Toronto Press, 1974)
Considering all sources of energy and the major world markets, these papers from energy economists in the United States, Canada, and Britain all indicate that the 1973 energy 'crisis' was and is a short-run problem caused by government action or inaction. Past policies are analysed, and future policies recommended.